Child Education Concept from The Perspective of Qira’ah Mubadalah - Abdullah Ahzami; Mistura; Putri Nisfi Siagian; Ade Naelul Huda (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2024)
The Holy Quran teaches universal values that are not limited to a specific race or gender. Allah, the Exalted, created humans in pairs to foster mutual understanding between them. Similarly, parental responsibility for child education should not be delegated to one party alone while the other remains indifferent. Among the societal phenomena is the stigma that the father's duty is solely to provide financially, while child education is entirely the mother's responsibility. Child education is considered a parental responsibility that encompasses various aspects, including faith, morals, physical, and social aspects. The concept of equality or "mubadalah" is highlighted as a framework that encourages fair cooperation and participation between men and women in the context of child education. In this context, equality is interpreted as mutual collaboration in raising children and in the interpretation of Islamic texts. Research is conducted to apply the "qira'ah mubadalah" approach in the context of child education. Gender equality and fair roles between men and women in child education are the primary focus of this research.